The Challenge of Religious and Social Identity in the Contemporary World - Reihaneh Sadat Raeis Alsadaty (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2020)
Religious identity as one of the types of identity has a close relationship with social identity and encompasses the expectations of one's religion in the individual and social domain. This is why scholars have attempted to theorize the presence of religion in the contemporary world, and since decades ago, various terms have been used to explain the emergence of religion, and some have spoken of the post-secular era. The concept of post-secularism, which has been followed by secularism, has justified the possibility of religion being present in public culture, but with the precondition that presence in social space should not extend to the political sphere and social structures.